A systematic review of the measurement of infant posture and movement using image or video data analysis - Sermpon, Nisasri; Gima, Hirotaka (Archives of Allied Health Sciences, 2022)
Gross motor skill development (spontaneous movement and posture) is the most basic assessment domain for infant body control and movement skills. Image or video analysis in early infancy is an alternative quantitative and qualitative method for assessing movement with the advantages of being cost-effective, requiring less set-up time without attaching markers, assessing natural movement, and availability in clinical settings. This study aimed to review novel methods for measuring posture and movement of infants using image or video analysis, focusing on studies that used the markerless technique. PubMed and EBSCO were searched using three main keywords (‘infants’, ‘posture and movement’, and ‘measurement’). Articles from other sources were screened and included, and a manual search was performed. Ultimately, 25 articles published since 2010 were selected. The outcomes of this review primarily focused on study purpose, subject information and position, recording tools, analysis techniques, and study features of interest. Image or video data analysis, primarily using two-dimensional and depth video cameras, was used for clinical investigation and technical evaluation, assuring assessment and treatment methods based on quantitative results. Infants aged 0–6 months were evaluated in the supine position in the studies in this review, with an analysis technique that was primarily computer-based. The parameters included variations regarding program or software; for example, the quantity of motion, the centroid of motion, area, velocity, acceleration, and coordinates. Regarding the advantages of using 2D video data analysis for natural movement assessment, further studies and novel technologies are required for clinical practice.